The profitability of farm sales in Poland compared to the countries of the European Union - Ryś-Jurek, Roma (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2013)
The purpose of the article was to compare the profitability of sales from agricultural sector holdings in Poland and in the European Union. It uses statistical data from the FADN database collected for commercial farms. This enabled an analysis of the phenomenon in the European Union between 2005–2009 and of systems by: economic size, type of farming and production conditions. Research of the Polish FADN regions was also conducted.
Keywords: agricultural farm; return on sales; European Union